HUBUNGAN ANTARA PROFIL LIPID DAN HIPERTENSI PADA PENDERITA STROKE ISKEMIK DI RSUP SANGLAH DENPASAR TAHUN 2014 - Putra Kamajaya, Gde Ary; Lestari, AA Wiradewi; Sutirta Yasa, I Wayan (E-Jurnal Medika Udayana, 2016)
Stroke is one of cerebrovascular diseases that categorized as a number one cause of long-term disability in the world. Dyslipidemia are risk factors for the formation of atherosclerosis. Atherosclerosis will make clogs and congested of fat or blood clots. That will cause a higher systemic vascular resistance and lead to increased blood pressure. Goal of this study to prove the existence of differences in levels of systolic and diastolic blood pressure in patients with ischemic stroke with normal lipid profile and dyslipidemia in Sanglah Hospital January - Desember 2014. This study is cross sectional and analytic observational study. There are 87 samples collected through consecutive sampling and data were analyzed with Mann Whitney test. There are 87 samples consist of 57.5% male, and 42.5% female; 25% samples <49 years old  and 75% samples ?49 years old. Fifty five percent patients showed BMI 18.50 to 24.90 kg/m 2 , 31% patients had history of heart disease, and 36.8% had history of diabetes mellitus. There is a significant mean difference of systolic blood pressure levels among patients wih normal lipid profiles compare with hyper-LDL (p=0.019) in Ischemic Stroke patients. There is also significant mean differences of diastolic blood pressure levels among patients with normal lipid profiles compare with hypercholesterolemia (p=0.015) in Ischemic Stroke patients. Our study highlight that there are significant differences of  systolic blood pressure levels in Ischemic Stroke patients with normal lipid profiles compare with hyper-LDL and significant differences of diastolic blood pressure levels in Ischemic Stroke patients with  normal lipid profiles compare with hypercholesterolemia (p<0.05).
Keywords: Ischemic Stroke, Lipid Profile, Total Cholesterol, LDL Cholesterol, Systolic Blood Pressure, Diastolic Blood Pressure